Construct validation of the portuguese version of the restraint scale - Carvalho, J. (2016)
The main purpose of this study was to adapt the Restraint Scale (RS) to Portuguese and examine its psychometric properties, specifically its construct validity. Method: In this study, 238 normal-weight adults (82% women; Mean age = 36.6, SD = 15.0) participated in an online survey containing measures of Restraint Scale, Three Factor Eating Questionnaire, Dutch Eating Behaviour Questionnaire, and Body Dissatisfaction and Drive for Thinness scales. Results: Exploratory factor analyses corroborated the two-factors structure found in previous studies, in particular when three items without clear factorial assignment and low correlation were excluded. A final two-factors version of the RS containing seven items presented a very good fit to the measurement model and good internal consistency. Confirmatory factor analysis of the 7-items RS in relation to a three-factor model of overeating, dieting and body dissatisfaction measures revealed that the RS was the only restraint measure loading in all three factors. Conclusion: This suggests that the 7-items Portuguese version of the RS has good psychometric properties and unique features that lend it appropriate to identify and study unsuccessful chronic dieters.